2022
DOI: 10.1007/s13300-022-01307-y
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Early and Universal Screening for Gestational Diabetes Mellitus: Findings from 9314 Pregnant Women in a Major City in Nigeria

Abstract: Introduction: Risk-based screening has been replaced by universal screening as the recommended course of care for gestational diabetes mellitus (GDM). As of 2016, no state in Nigeria had implemented a policy of universal screening for GDM. This research aimed to assess findings from a universal screening programme and its implication for scaling up universal and early screening for GDM. Methods: This was a descriptive cross-sectional study conducted in Rivers State Nigeria between February 2017 and January 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…About one in every three women diagnosed with GDM was diagnosed before 24 weeks, which is lower than previous findings that one in every two women diagnosed with GDM was diagnosed in the first and second trimesters [ 9 ]. These findings support early screening for GDM, which will detect women who develop GDM before 24 weeks and would have been missed by universal screening after 24 weeks.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…About one in every three women diagnosed with GDM was diagnosed before 24 weeks, which is lower than previous findings that one in every two women diagnosed with GDM was diagnosed in the first and second trimesters [ 9 ]. These findings support early screening for GDM, which will detect women who develop GDM before 24 weeks and would have been missed by universal screening after 24 weeks.…”
Section: Discussioncontrasting
confidence: 66%
“…In the present study, the prevalence of GDM was 7.8%, which is lower than the pooled prevalence of GDM in Nigeria reported in a systematic review (11%), and this was attributed to differences in female characteristics of the study participants and differences in the screening methods utilized [ 8 ]. A prevalence of 5.2% was also reported and it was concluded that the prevalence of GDM in Nigeria was on the rise and that the disparities in prevalence reports could be attributed to better screening tools, better screening policies, and increased exposure to risk factors [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the impact of GDM and its complications on both maternal and fetal well-being, the need for universal screening via Oral Glucose Tolerance Test (OGTT) becomes evident. Due to its proven benefit over risk factor-based screening, universal screening is highly recommended, even in early pregnancy, given availability of financial, material, space, and human resources [ 9 , 10 ]. However, implementing oral glucose tolerance testing during pregnancy for all women, and more than once in some, is both operationally challenging and costly, hence the continued emphasis on the need to improve risk factor-based screening approach in most developing countries especially in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%